Price Behaviour of Spot and Futures Markets for Commodities in India : Case of Soy Oil - Ajoy Kumar, M.; Shollapur, M. R. (Indian Journal of Research in Capital Markets, 2015)
The purpose of this paper was to study the relationship between the spot and futures prices of soy oil - the most actively traded commodity in the futures market in India. It aimed to test whether the futures market is fulfilling the price discovery function, which is important for providing an effective hedging platform. Data related to daily prices of spot and futures markets were used to analyze the long-run and short-run relationship. Cointegration, vector error correction model , and bivariate BEKK-GARCH model were applied to examine the relationship between the returns and volatilities of both the markets. The study found existence of a long-run equilibrium relationship between the spot and futures markets. We also observed that the futures market played a lead role in the price discovery function. In the short-run, the volatility spillover from the spot market to futures was found to be strong. The findings of this study are of significance to hedgers who can design appropriate hedging strategies based on the volatility behaviour.